The DEMPE concept and intangibles definition, practical approach and analysis in the context of licence model - Dziwiński, Karol (Kluwer Law International B.V., 2022)
"Under the widely applied rules of the OECD Transfer Pricing Guidelines, allocation of the returns from the exploitation of intellectual property should be shared among all entities that contribute towards the profit-generating value of an intangible. This important book, in its detailed treatment of compliance with this principle - known as DEMPE (development, enhancement, maintenance, protection and exploitation) - describes exactly how both taxpayers and tax authorities can achieve an accurate assessment of transactions in order to arrive at an appropriate transfer pricing outcome. Analysing the legal, economic, and business management aspects of multinational enterprises activities, the book provides a comprehensive understanding of the DEMPE concept both in theory and in practice. Fully covered are such issues and topics as the following: role of the DEMPE concept within the framework of international tax law and transfer pricing; interplay of the DEMPE concept with the arm's length principle; full description of each DEMPE function and analysis in the light of possible tax and transfer pricing consequences; modes of application of the DEMPE concept which can be directly implemented in practice; and additional tools (e.g., value chain analysis or RACI matrix) useful in applying the DEMPE concept. The book also provides the first in-depth analysis of the interplay between the DEMPE concept and the licence model in its various structural variations. Taking into account that intangibles amount to 84% of the market value of the S&P 500 companies and that over 80% of global trade transactions can be linked to value chains of multinational enterprises - and recognizing the scarcity of guidance heretofore on the application of the DEMPE concept - tax advisors, corporate counsels, tax authorities, and academics around the world are sure to appreciate and benefit greatly from this matchless and practical book."--